Hubungan Religiusitas dan Resiliensi Akademik pada Mahasiswa dalam Perspektif Psikologi Islam - Nadhifah, Firyal; Karimulloh, Karimulloh (Al-Qalb : Jurnal Psikologi Islam, 2021)
Abstract:Â In college education, certainly the students will face difficulties or challenges. In order to overcome every challenge and difficulty well, students need the academic resilience in themselves. One of the internal factors that impact the academic resilience is religiosity. This study aims to see the relation between religiosity and academic resilience in students in the perspective of Islamic psychology. This research uses library research method. The result of this research is that religiosity is one of the factors that affect the academic resilience, In Islam, individuals with good religiosity will believe that God will not give a difficulty beyond the limits of someones ability and the individual also realizes that every difficulty there must be ease afterwards, as long as the individual is willing to try, pray, and be patient. In other words, individuals with good religiosity will be able to solve the difficulties or problems in their lives.